2000
DOI: 10.1002/1520-636x(2001)13:1<56::aid-chir11>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective correlation between retention factor and lipophilicity index in chiral separation on cellulose and amylose tris(3,5-dimethylphenylcarbamate) CSPs in reversed mode: A case study

Abstract: For a series of alkyl substituted N-arylthiazoline-2-(thi)one atropisomers 1-14, lipophilicity indexes log kw obtained by polycratic RP-HPLC were compared to ln k(+)-S and ln k(-)-R obtained on CHIRALCEL OD-R(R) (reversed mode) and CHIRALPAK AD-RH(R) (reversed mode). Linear correlations were obtained in most cases. It appears that the correlation lines for R and S enantiomers may be parallel, convergent, or divergent, accounting for the observed alpha variation in going from methyl to tert-butyl series. Some t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…In other words, whatever the effect on retention, increasing lipophilicity was favorable, to a certain extent, on both CSP. This is in agreement with previous observations from Roussel and coworkers who observed that retention on these two CSP could be related to lipophilicity. However, it may be observed that the enantioseparation values remained moderate on Chiralcel OD‐H while they were higher, and increased at a faster rate on Chiralpak AD‐H as appears when the scales of the figures are compared.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In other words, whatever the effect on retention, increasing lipophilicity was favorable, to a certain extent, on both CSP. This is in agreement with previous observations from Roussel and coworkers who observed that retention on these two CSP could be related to lipophilicity. However, it may be observed that the enantioseparation values remained moderate on Chiralcel OD‐H while they were higher, and increased at a faster rate on Chiralpak AD‐H as appears when the scales of the figures are compared.…”
Section: Resultssupporting
confidence: 94%
“…However, it may be observed that the enantioseparation values remained moderate on Chiralcel OD-H while they were higher, and increased at a faster rate on Chiralpak AD-H as appears when the scales of the figures are compared. This is also in accordance with Roussel's suggestion that the two phases may have different hydrophobic pockets [23]. Additionally, the retention and separation behavior on Chiralpak AD-H for this homologous series was not influenced by temperature changes in the range studied (5-40 • C) while some changes could be observed with Chiralcel OD-H.…”
Section: Retention Behavior Of Phenylthiohydantoin Amino Acids With Asupporting
confidence: 90%
“…Other works conducted in HPLC on polysaccharide stationary phases have shown that increased lipophilicity could result in either increased or decreased enantioseparation. 27 We have shown in past studies that enantiorecognition on cellulose tris-(3,5dimethylphenylcarbamate) in SFC conditions close to those used here was unaffected by molecular volume, while bulkiness was a significant factor in deteriorating chiral recognition. 28 Thus we prefer this explanation: Steric constraints might be participating in the separation mechanism and it could be expected that the bulky t-butyl groups are somewhat restricting the access of the compounds to some chiral cavities, causing limited enantioresolution for these compounds.…”
Section: Influence Of Solute Structure On the Chromatographic Behaviormentioning
confidence: 57%
“…Increasing molecular volume may have different effects on enantioseparations: Either it is providing extra opportunities for dispersive interactions, contributing or not to improved enantiorecognition, or it is causing a steric constraint limiting the access to chiral grooves, thus impairing chiral recognition. Other works conducted in HPLC on polysaccharide stationary phases have shown that increased lipophilicity could result in either increased or decreased enantioseparation . We have shown in past studies that enantiorecognition on cellulose tris ‐(3,5‐dimethylphenylcarbamate) in SFC conditions close to those used here was unaffected by molecular volume, while bulkiness was a significant factor in deteriorating chiral recognition .…”
Section: Resultsmentioning
confidence: 74%
“…In summary, a combination of hydrophobic interactions, hydrogen bonding, dipoledipole interactions, and charge transfer (π-π) formation is believed to explain the chiral recognition mechanisms. [27][28][29][30] The difference in the chiral recognition ability between the amylose and the cellulose may be due the difference in the polysaccharide configuration. Amylose possesses a more helical configuration than cellulose that is more rigid and linear in nature.…”
Section: Enantioseparation Of the 4iminonaringenin Derivativesmentioning
confidence: 99%